The ugly duchess beauty & satire in the Renaissance - Capron, Emma; Clayton, Martin 1967-; Wytema, Charlotte (National Gallery Global, 2023)
Quinten Massys' An Old Woman ('The Ugly Duchess') is one of the Renaissance's most famous faces. In a fresh review of the iconic image, this book unveils the painting's original context: its status as a pioneering work of satirical art, its debt to Leonardo da Vinci's grotesque drawings, and what it tells us about the period's complex attitudes towards women, age and normative beauty. The painting and its partner, An Old Man, are parodic portraits that mock the supposed lust and vanity of older women. Yet a closer look also reveals a figure defiantly flouting conventions and a painter subverting artistic expectations. The publication traces the eventful afterlife and enduring power of this seminal image: how she gained her nickname 'The Ugly Duchess' and inspired John Tenniel's much-loved illustrations of Lewis Carroll's Alice's Adventures in Wonderland (1865), capturing the imagination of generations of readers. Exhibition: National Gallery, London, UK (16.03. ? 11.06.2023)
Auf der Titelblattrückseite: "Published to accompany the exhibition: 'The Ugly Duchess: Beauty and Satire in the Renaissance', The National Gallery, London, 16 March-11 June 2023"
Keywords: Massys, Quentin -- 1466-1530 -- Brustbild einer hässlichen Frau; Tenniel, John -- 1820-1914; Carroll, Lewis -- 1832-1898 -- Alice's adventures in Wonderland; Geschichte 1450-1550; Illustration; Brustbild; Physiognomie -- Motiv; Satire; Rezeption; Karikatur; Das Hässliche; Kunst; Frau -- Motiv; Metsys, Quentin / 1465 or 1466-1530 / Exhibitions; Metsys, Quentin / 1465 or 1466-1530 / Ugly duchess; Painting / Belgium / Exhibitions; Painting; Belgium; Exhibition catalogs; Ausstellungskatalog -- The National Gallery -- 16.03.2023-11.06.2023 -- London